Submental tracheal intubation in a school-age child with maxillofacial trauma: Our techniques and devices. Issue 6 (November 2022) - Ishida, Shintaro; Kita, Ryosuke; Hashiguchi, Shiho; Mano, Ryosuke; Nakamura, Shinsuke; Yoshino, Aya; Aoyagi, Naoko; Shimamura, Tomoki; Kondo, Seiji
Abstract: Securing an airway in a severely school-age patient with maxillofacial trauma is quite challenging and is an important part of treatment. A particularly useful technique for airway management in pediatrics, planned submental tracheal intubation (STI), has often been reported. We employed this technique in an eight-year-old girl who required open reduction and internal fixation of the mandible fracture along with suffered midface and skull base fractures, leading to the prevention of serious complications, such as intracranial penetration, when manipulating a nasotracheal tube. We described the novel aspects of this technique, known as the 1–1–1 rule, in a school-age patient with severe maxillofacial injuries and demonstrated its utility along with a review of the literature.